Flouting Maxims on WhatsApp Group Chat and Its Pedagogical Implication in Language Teaching - Hieronimus Canggung Darong; Thi Loan Lam (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2026)
This study investigates the types and frequency of flouting maxims in WhatsApp group communication and examines their pedagogical implications for language teaching. Employing a qualitative discourse analysis approach, the study analyzed selected utterances produced by 27 members of a WhatsApp group over a six-month period. The data were categorized using Grice’s Cooperative Principle, particularly the maxims of Quantity, Quality, Relevance, and Manner. In addition to identifying instances of maxim flouting, the study also explored the communicative purposes behind such linguistic behavior and how participants interpreted implied meanings within their interactions. The findings show that all four types of maxim flouting occurred in the interaction. Flouting the Maxim of Quantity appeared most frequently, accounting for 45% of the data, followed by flouting the Maxim of Manner at 35%, flouting the Maxim of Relevance at 15%, and flouting the Maxim of Quality at 5%. These results indicate that participants often used excessive information, indirectness, ambiguity, exaggeration, and topic shifts to generate implicatures, express humor, maintain solidarity, and negotiate interpersonal relationships in digital communication. Furthermore, the analysis reveals that such pragmatic strategies are influenced by contextual factors such as group familiarity, shared knowledge, and the informal nature of online communication platforms. The study also highlights that participants rely heavily on implicit cues, emojis, and shared cultural references to convey meanings that go beyond literal interpretations, demonstrating the dynamic nature of digital discourse. Additionally, the findings suggest that the asynchronous nature of WhatsApp communication allows users more flexibility in crafting responses, which may contribute to the frequent occurrence of maxim flouting as a deliberate communicative choice. The study concludes that flouting maxims in WhatsApp group chats should not merely be viewed as communication failure, but as a pragmatic strategy shaped by context and social interaction. Pedagogically, the findings suggest that authentic digital conversations can be used as instructional materials to develop learners’ pragmatic awareness, discourse competence, and context-sensitive communication skills. Incorporating real-life examples of digital discourse into classroom activities may help learners better understand implied meanings, interpret indirect language, and respond appropriately in various communicative situations, thereby enhancing their overall communicative competence in both online and offline contexts. Furthermore, integrating such materials into language instruction can encourage learners to critically analyze communication patterns, recognize pragmatic nuances, and apply these insights in their own interactions, ultimately fostering more effective and meaningful communication skills in diverse social settings.